Legal Protection for Soccer Supporters in Riots at Gelora Joko Samudro Stadium in Gresik - Qalbi Alif Syah Putra; Deni Setiyawan (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The research discussed the legal protection for supporters who became victims at Gelora Joko Ocean Stadium by treating supporters as legal subjects in sports activities. This research aims to analyze the legal protections provided by legislation, the responsibilities of officials, the safety of supporters, including matches and clubs, and the obstacles to their implementation. The method used is a jurisdictional research approach, drawing on legislation, cases, empirical studies, and conceptual work. Data were obtained through interviews, field observations, and documentation of legislation and related legal documents. Research results indicate that legal protection for supporters is provided in the Act and the Book of Criminal Law, but implementation remains suboptimal. Weak law enforcement, lack of coordination between parties, lack of law, officials, and clubs in running responsibility, and the club in running responsibility for supporters. This research concluded that the legal protection for supporters is still adequate, although Law Number 11 years has given support and participation to the coordination and participation in the coordination.